Penentuan Status Mutu Air Metode Storet DAS Kali Curah Macan - Saiful Anwar; Budi Hariono; Michael Joko Wibowo; Merry Muspita Dyah Utami (Politeknik Negeri Jember, 2018)
The monitoring station of Curah Macan Watershed is located in Arjasa Village, Arjasa District, Situbondo Regency with 7o71'66